Galerie Contour. - Geirlandt, Karel J. (Brussel : Galerie Contour.)
Raveel, Roger ; Dekeyser, Raoul ; Elias, Etienne ; Van Lint, Louis ; Somville, Roger ; Delahaut, Jo ; Cobbaert, Jan ; Theys, Yvan ; Axell, Evelyne ; Dierickx, Karel ; Ghysels, J.P. ; Kulche, Gust ; Sarnari, Franco ; Mattia, Gianluigi ; Mulas, Franco ; Ciniglia, Giulio ; Turchiaro, Aldo
biografie
Frans & Nederlands
boek